Trade, policy, and food security - Smith, Vincent H.; Glauber, Joseph W. (International Association of Agricultural Economists, 2020)
Food insecurity is extensive throughout the world and hunger and malnutrition are expected to remain serious humanitarian and political concerns, both in the short term and for the foreseeable future, particularly in low income developing countries where many rural and urban households are both income and asset poor. In those countries, domestic agricultural production is expected to be especially vulnerable to the impacts of climate change over the next 30 years. Thus international markets for staple agricultural commodities, which have become increasingly important as sources of nutrition for both developing and developed countries over the past 60 years, are likely to become even more important in the future. Free trade policies allow countries to exploit their comparative advantages in economic activity, increasing average per capita incomes, longer term growth rates and a country's capacity to fund social safety nets for the poor. However, many countries abandoned those policies in favor of domestic protections in their efforts to mitigate the effects of short run food crises. The policy challenge is therefore to resolve the tension between optimal long run policies and short run initiatives to address food security concerns.